Autoinflation compared to ventilation tubes for treating chronic otitis media with effusion. (1st June 2022) - Moniri, Armin B.; Lino, João; Aziz, Luaay; Rosenfeld, Richard M.
Abstract: Background: Otitis media with effusion (OME) is the most common cause of acquired hearing loss and surgery in children. Autoinflation has been suggested as an alternative treatment for OME. Objectives: The aim of the study was to compare treatment outcome with a new autoinflation device versus ventilation tube (VT) surgery or watchful waiting in children with chronic bilateral OME from the waiting list for surgery. Methods: Forty-five children performed autoinflation during four weeks, forty-five were submitted to VT surgery, and twenty-three were enrolled as control group. Tympanometry was performed in the autoinflation and the control groups and audiometry in all groups. Results: An equivalent hearing improvement was achieved in the autoinflation and the VT group at one ( p =.19), six ( p =.23) and twelve ( p =.31) months with no significant alteration in the control group. In the autoinflation group 80% of the children avoided surgery and no complications were reported compared to 34% complication rate in the VT group. Conclusion: Autoinflation achieved an equivalent improvement in hearing thresholds compared to VT surgery for treating OME. Significance: Autoinflation may be a reasonable first-line treatment for children with OME to potentially avoid surgery. Article Summary: The Moniri autoinflation device is well tolerated and an effective alternative to ventilation tubes for treatment of chronic otitis media with effusion in young children. What's known on this subject: Previous studies have shown that autoinflation may reduce effusion in children with otitis media with effusion; however limited compliance to treatment, lack of adequate hearing evaluation, short follow-up time and also lack of comparative data to ventilation tube surgery have been reported. What this study adds: A new device was developed to allow for the performance of autoinflation in young children. The effect is compared to ventilation tube surgery and equivalent improvement in hearing is achieved in the short and the long-term follow-up.